Tenofovir-induced osteopenia and hyperparathyroidism: A case report and literature review - Zeng, Jing; Ye, Peng; Wei, Dong; Li, Lan; Ma, Wanxia (Frontiers in Endocrinology, 2023)
Tenofovir disoproxil fumarate is the first-line antiviral therapy for chronic viral hepatitis B, but long term use is associated with renal failure and hypophosphatemic osteomalacia. Tenofovir disoproxil fumarate-induced osteoporosis and secondary hyperparathyroidism are less commonly reported. Herein we describe the case of a patient with bone and multijoint pain who was initially misdiagnosed as having normocalcemic primary hyperparathyroidism associated with prolonged exposure to tenofovir disoproxil fumarate. The patient’s 24-h urinary calcium and phosphorus excretion levels and serum calcium levels were at the lower end of the normal range. After reviewing these findings, the diagnosis was amended to osteoporosis and secondary hyperparathyroidism caused by tenofovir disoproxil fumarate. In this report we describe the differences in clinical and laboratory manifestations of hyperparathyroidism induced by tenofovir disoproxil fumarate and normocalcemic primary hyperparathyroidism. We also discuss relevant pathophysiological mechanisms and propose a feasible treatment strategy.